Short Communication: Morphophysiological Response to Partial Submergence and Water Deficit in North Sulawesi Local Rice - Song Ai Nio; Christine J.R. Kakanga; Marlince Koda; Daniel Peter Mantilen Ludong (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2023)
Flood and drought are two disasters that resulted in crop failure, including rice production. The objective of this study was to evaluate the morphophysiological characteristics of North Sulawesi local rice (Oryza sativa L.) cultivars as response to partial submergence and water deficit at the vegetative phase based on plant height, number of leaves, root length and volume, and leaf total chlorophyll concentration. The factorial experiment in Completely Randomized Design consisted of four rice cultivars (Superwin, Ombong, Temo, and Burungan) and three treatments (well-watered, partial submerged, and water deficit). The treatments commenced at four-fully-expanded leaf stage for 14 days. Plant height and leaf number were recorded on day 0 (before the treatments commenced), 7, and 14 after treatments. The length and volume of roots as well as total chlorophyll were recorded at 14 days after treatment. Root length was potential indicator of partial submergence and water deficit as it was higher under partial submergence and water deficit than well-watered. Root volume was potential indicator of partial submergence as it was larger under partial submergence than water deficit and well-watered. The partial submergence and water deficit tolerance of North Sulawesi local rice should be further evaluated based on the other characteristics.AbstrakKebanjiran dan kekeringan merupakan bencana alam yang mengakibatkan kegagalan panen, termasuk produksi beras. Penelitian ini bertujuan untuk mengkaji karakterisitik morfofisiologis pada padi (Oryza sativa L.) lokal Sulawesi Utara sebagai respons terhadap kebanjiran dan kekeringan pada fase vegetatif berdasarkan tinggi tanaman, jumlah daun, panjang, dan volume akar serta kandungan klorofil daun. Percobaan faktorial dalam Rancangan Acak Lengkap ini menggunakan empat kultivar padi (Superwin, Ombong, Temo, dan Burungan) serta tiga perlakuan (diairi, digenangi, dan tidak diairi). Perlakuan dimulai pada saat tanaman mempunyai empat daun yang berkembang penuh selama 14 hari. Tinggi tanaman dan jumlah daun diamati pada hari ke-0 (sebelum perlakuan dimulai), hari ke-7, dan 14 setelah perlakuan. Panjang dan volume akar serta kandungan klorofil daun diukur pada 14 hari setelah perlakuan. Panjang akar merupakan indikator yang potensial untuk kebanjiran dan kekeringan karena panjang akar saat kebanjiran dan kekeringan lebih besar daripada diairi. Volume akar merupakan indikator yang potensial untuk kebanjiran karena volume akar saat kebanjiran lebih besar daripada saat kekeringan dan diairi. Toleransi padi lokal Sulawesi Utara terhadap kebanjiran dan kekeringan perlu dievaluasi lebih lanjut berdasarkan karakteristik lainnya.